Application of Netmapping and Fuzzy Cognitive Mapping to explore factors impacting low-emission food system in Qingshan Village, China - Kumar, Praveen; Wang, Xinxin; Chen, Kevin Z. (CGIAR, 2023)
From November 3rd through 9th, 2023, mental modeling exercises, led by scholars and researchers from the Zhejiang University, were conducted by engaging with stakeholders of the Qingshan Village of Zhejiang province in China as part of a collaborative project on the Living Labs for People (LL4P) work package in the CGIAR Research Initiative on “Low-Emission Food Systems” (Mitigate+). The overall objective of the study was to explore potential barriers and enablers helping the development of a low-emission food system in Qingshan Village. The Qingshan Village is a rural community developing a green economy by integrating sustainable farming, ecosystem travel, traditional culture protection, environment protection, and local agri-food value chain. However, based on the preliminary field visits, it was concluded that key stakeholders have incoherent perceptions, particularly on what it means to have a low-emission food system. A clear understanding of the determinants contributing to a low-emission food system among key stakeholders is central to the community’s economic development and the evolution of Qingshan as a “Future Village.” Rural communities with similar objectives to realize low-emission food systems can leverage the conceptual model developed in this research. The specific objectives guiding the study were to: 1) Unpack key indicators of a low-emission food system in the Qingshan village, 2) Explore factors impacting the development of a low-emission food system, and 3) Model the dynamics of low-emission food systems based on the mental models of key stakeholders.